DRAMATURGY OF UKRAINIAN DIASPORA OF THE FIRST HALF OF THE 20 th CENTURY: STYLE ASPECT - Semak, O. І. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article has the analysis of peculiarities of style evolution in drama written abroad in the first half of the XX century. It has regularities which give us an opportunity to speak about phenomenon of original style of dramatic art in emigration.